The Effect of @schoters Social Media Content : How Gen Z's Social Engagement Shapes Scholarship Choices - Wilda Fitriana; Mega Agnesti; Meilani Rahmah; Khaerudin Imawan; Dedet Erawati (Asian Journal of Social and Humanities, 2024)
Currently, generation Z is literate about their education and career path in the future, where with the increasing cost of education in higher education, scholarships are the right solution. However, the fact in the mash field is that there are prospective students who do not know how to access scholarship information. Schoters is one of the providers of scholarship information and study abroad preparation guidance services. This research aims to find out how generation Z gets scholarships and the role of schoters that motivates generation Z to get scholarships. This study uses a qualitative research method with the theory of uses and gratification where currently it is no longer looking at the media to the audience, but what the audience does to the media, now individuals use mass communication to meet their needs. Where the result of this study is that schoters has succeeded in helping thousands of its students qualify for scholarships to study abroad as evidenced by the many success stories shared on schoters' social media, so it can be concluded that.